Modeling of physical phenomena as a methodological means of forming a knowledge structure in physics and programming - Holovina, Nina; Holovin, Mykola (State Higher Educational Institution "University Education Management", 2021)
To bring the theoretical basis to the improvement of the methodic of carrying out laboratory works in physics and computer sciences, a study of psychological and cognitive processes that accompany the corresponding educational activity was held. The important moment of the work is the research of the mental side of educational activities in the terms of formal logic. The accompanying steps to these mental activities and the talk activity are considered. The content component of the talk activity was considered in the work as an important diagnostic factor that indicates the level of understanding of the nature of the new material or the completion of the corresponding cognitive structure. The original graphical ways of formalization of the cognitive scheme of the object activity and the logic of its formation in the context of mental and materialized education activities are presented. These ideas were used to consider the processes of educational activity on the example of the creation of a simple physical model that is realized through the Python talk with the help of Visual library. Educational activities are considered through the prism of the evolution of the structural organization of mental representation of the objects of this activity. The research demonstrates the cyclical nature of the corresponding cognitive processes, materialized activities, and hierarchical character of the structure of knowledge that is formed in the process of educational activities in physics and programming. The correlation of these processes with the dynamics of the evolution of knowledge is settled. The conceptual ideas that could be useful for modifications of the methodic of realization of laboratory knowledge in the direction of modeling of physical processes and phenomena are formulated. Individual algorithmic problems of modeling of physical processes are considered in the research as components of the holistic system of problems. According to the point of view of the authors, in the course of the preparation of highly professional specialists in the domain of natural sciences, it is necessary to devote a lot of time to the conscious, goal-oriented formation of protocols of abstract logical and causal thinking. The methodology of such work is well formulated, especially in the well-known methods of descending step-by-step detailing and in modular programming
Keywords: methods of teaching physics; mental; materialized actions; hierarchy; evolution of knowledge structure; 53:004.942